Assessment of the Impact of Fiscal Policy on Economic Growth in the Republic of Armenia - M. A. Voskanyan; A. G. Galstyan (Финансы: теория и практика, 2023)
Fiscal policy plays a crucial role in ensuring economic growth and development in the country and overcoming economic recessions. The subject of the research is the tax system in the Republic of Armenia. The study aims to identify and assess the impact of the fiscal policy on economic growth in the Republic of Armenia. Since the global financial crisis of 2008, the Armenian economy has been in stagnation, reaching pre-crisis GDP levels only in 2018. Both theory and practice point to the ambiguous nature of the impact of fiscal policy on economic growth. At the same time, the 2020 crisis caused by the pandemic exacerbated the situation by focusing the attention of economists on fiscal policy to stimulate the real sector of the economy, which justifies the relevance of the current study. The paper’s novelty lies in assessing the impact of certain types of taxes on the economic growth rates in Armenia. To achieve the goal of the study, the authors use such methods as a comparative analysis of foreign studies and systemic and statistical analysis. To econometrically assess the impact of taxes on economic growth in the country, a vector autoregression (VAR) model was applied. As a result of the study, the authors found that both tax regulation in general and the individual taxes are restrictive in nature and have a negative impact on economic growth in the country. The authors conclude that such a restrictive policy has led to a slowdown in economic growth in the Republic of Armenia over the past decades